FEAR SYNDROME AND ATTITUDES TOWARDS DEATH IN YOUNGER AND OLDER FEMALES - Lipinski, Stanislaw (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The author has measured attitudes regarding death and fear syndrome in a group of females of young and of old age. The results obtained via the Student's t-test reveal that older females demonstrate perceive death in the categories of value, inevitability and centrality, whereas younger females see it as tragic, absurd, mysterious and fearful.Regarding the fear syndrome older females demonstrate a higher level of hidden fear (HF) and a significantly higher level of needs and desires (Q4+), while younger females – a significantly higher level of neurotic tendencies (C-). The correlation between fear syndrome and attitude towards death also differentiate both examined groups. The attitude of the young females is marked mostly by fear.